Dexter lawn and exterior of Engineering West (Building 21) (1972)
Dexter lawn is pictured as well as the exterior of Engineering West (Building 21), as well as Building 14. The trash can to the left says, 'Cal Poly: Let's Keep Our Campus Clean'.